2017
DOI: 10.1101/208066
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FERMI: A novel method for sensitive detection of rare mutations in somatic tissue

Abstract: With growing interest in monitoring mutational processes in normal tissues, tumor heterogeneity, and cancer evolution under therapy, the ability to accurately and economically detect ultra-rare mutations is becoming increasingly important. However, this capability has often been compromised by significant sequencing, PCR and DNA preparation error rates. Here, we describe FERMI (Fast Extremely Rare Mutation Identification) -a novel method designed to eliminate the majority of these sequencing and library prepar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Tong et al 8 also reported detection of CH in individuals with DS at the 2018 Annual Meeting of the American Society of Hematology. We compared our results for the typical population with those from Liggett et al 7 and Young et al 9 (who used similar error-corrected sequencing methods), limiting our analyses to only mutations detected within the regions we probed in this study; similar rates of expansions and VAFs are observed for typical populations across studies (Figure 1E), with the caveat that the number of individuals is limited, and most of these individuals were older. Of note, we also analyzed 6 typical individuals as controls in this validation cohort, none of whom exhibited CH (supplemental Table 1).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Tong et al 8 also reported detection of CH in individuals with DS at the 2018 Annual Meeting of the American Society of Hematology. We compared our results for the typical population with those from Liggett et al 7 and Young et al 9 (who used similar error-corrected sequencing methods), limiting our analyses to only mutations detected within the regions we probed in this study; similar rates of expansions and VAFs are observed for typical populations across studies (Figure 1E), with the caveat that the number of individuals is limited, and most of these individuals were older. Of note, we also analyzed 6 typical individuals as controls in this validation cohort, none of whom exhibited CH (supplemental Table 1).…”
Section: Resultsmentioning
confidence: 96%
“…To define the frequency of CH in DS, we used the previously described Fast Extremely Rare Mutation Identification (FERMI) error-corrected and targeted sequencing approach, which enables detection of rare somatic mutations present in at least 1 in 10 000 cells. 7 By using FERMI, we analyzed genomic regions (;5 kb total) that are often disrupted in CH and/or acute myeloid leukemia (AML) to quantify hematopoietic clones that have undergone clonal expansion.…”
Section: Introductionmentioning
confidence: 99%
“…There are many ways to impair tissue functionality, as observed in non-malignant and malignant blood disorders. A recently uncovered phenomenon called clonal hematopoiesis provides an illustrative example of how increasingly sensitive genomics approaches can reveal key perturbations to hematopoiesis and provide new insights into this process (Figure 3; Jaiswal and Ebert, 2019;Liggett et al, 2019).…”
Section: Clonal Hematopoiesismentioning
confidence: 99%
“…The one dimensionality of individual genomes is now being expanded by the possibility of massive parallel sequencing for somatic variant analysis and by single-cell or lineage-specific genotyping; culminating in a genotype spectrum. In whole blood, virtually every nucleotide position may be mutated across 10 5 cells [3]. Mapping one's genotype across multiple cell types and at several periods during a person's life may soon be feasible [4].…”
Section: Introductionmentioning
confidence: 99%